2021
DOI: 10.21107/infestasi.v17i1.9626
|View full text |Cite
|
Sign up to set email alerts
|

Fraud Prevention Mechanism: Enhancing From Religiosity, Whistleblowing Protection, and Whistleblowing Intention

Abstract: This This research aims to determine fraud prevention from religiosity, protection whistleblower, and whistleblowing system perspectives. The population in this research was employees of PT Prudential Life Assurance. The population is taken without distinguishing gender, education, and work experience and taken from 43 as the total number of insurance employees. This study used saturated samples or census as the sampling technique, whereas all population employs as samples. The research data uses primary data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(42 reference statements)
0
0
0
Order By: Relevance
“…Several studies have shown that religiosity impacts whistleblowing (see : Huang et al, 2021;Jayanti et al, 2021). Meanwhile, other studies have shown the opposite result: religiosity does not affect whistleblowing (see : Prasetyono et al 2021;Karlina et al, 2021).…”
Section: Introductionmentioning
confidence: 96%
“…Several studies have shown that religiosity impacts whistleblowing (see : Huang et al, 2021;Jayanti et al, 2021). Meanwhile, other studies have shown the opposite result: religiosity does not affect whistleblowing (see : Prasetyono et al 2021;Karlina et al, 2021).…”
Section: Introductionmentioning
confidence: 96%